2006
DOI: 10.1590/s0034-72992006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Redução do limiar de reflexo acústico em neonatos sem risco auditivo

Abstract: The auditory sensitization, a tool used in the investigation of acoustic reflex, allows the decrease of acoustic reflex thresholds from a facilitating stimulus. It may be presented before or simultaneously with the elicitor tone. The thresholds after and before the facilitating stimulus are compared and it is expected to see the decreased threshold. From the study of the acoustic reflex it is possible to obtain information about the auditory pathways, such as structures of the brainstem, since the acoustic ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
7
1
1
Order By: Relevance
“…In this study, for newborns in Group I, the mean ASRT obtained with the 226 Hz probe was lower (Table 1) in all frequencies in comparison to that found by other studies (14,24) . With the 1,000 Hz probe, the average was 74.2 dB for the 1,000 Hz frequency and 62.9 dB for 2,000 Hz (Table 1).…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…In this study, for newborns in Group I, the mean ASRT obtained with the 226 Hz probe was lower (Table 1) in all frequencies in comparison to that found by other studies (14,24) . With the 1,000 Hz probe, the average was 74.2 dB for the 1,000 Hz frequency and 62.9 dB for 2,000 Hz (Table 1).…”
Section: Discussioncontrasting
confidence: 71%
“…The reflexes were detected more successfully among infants when the correlation was calculated in 1,000-8,000 Hz, and among adults, from 250 to 2,000 Hz. The ipsilateral reflex threshold was analyzed (14) in the 1,000, 2,000, and 4,000 Hz frequencies, with the 226 Hz probe, and it was observed that for the female gender and the right ear, the mean dB (±standard deviation) was 96. 43 There was no significant difference between gender and frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acoustic reflexes involve auditory nuclei of the encephalic trunk, which relate to auditory processing skills. Acoustic reflex alterations may, therefore, indicate an alteration in one of these nuclei and, consequently, in auditory processing skills such as locating, selective attention and speech with background noise (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the considerations made above, we emphasize the need to carry on more tympanometry researches in neonates making use of both test conditions (226 e 1000 Hz). It is possible to research the thresholds of the acoustic reflexes in beast-fed babies, or even in the neonatal period, and, therefore, obtain information about the auditory pathways (10,15) . In literature there are studies which demonstrate the presence of contralateral acoustic reflex in neonates (20) , while there are others which demonstrate the presence of ispilateral acoustic reflex in breast-fed babies (6,21,22) .…”
Section: Introductionmentioning
confidence: 99%